Adverse event related to extravasation of vesicant solution in peripheral venous catheter - Silva, Amanda Stefani Torquato da; Pinto, Regiane de Lima Gasques; Ribeiro, Jorge Elias de Freitas; Possa, Juliana; Silingovschi, Guilherme Liberati; Gregolin, Maria Ângela Zamora Arruda; Buriola, Aline Aparecida; Camargo, Raquel Mori Pires de (Seven Editora, 2023)
Objective: to describe the experience of a patient who experienced a moderate adverse event related to the extravasation of vesicant solution in a peripheral venous catheter. Method: Descriptive exploratory research, with a qualitative approach, established by Resolution 466/12 of the National Health Council, approved by the Ethics Committee in Research involving Human Beings of the Universidade do Oeste Paulista, opinion No. 3,633,405 and CAAE protocol No. 20222619.9 .0000.5515 and signature of the Free and Informed Consent Form. Result: The extravasation of vesicant medication results in several damages to the patient, such as an extension of hospitalization time, increasing risk of infection, reduced limb functionality, financial losses, physical and emotional suffering in addition to the support of the institution, the multidisciplinary team and the family were essential in this recovery process. Conclusion: It is up to the nurse to carefully assess the risks of phlebitis and extravasation of vesicant drugs in their patients, guiding them and managing the risks during this process, in addition, to training their entire team regarding these complications and proposing necessary preventive care. DOI:https://doi.org/10.56238/devopinterscie-233